KUALITAS FISIK RUMAH PENDERITA TB PARU DI WILAYAH KERJA PUSKESMAS I KEMBARAN KABUPATEN BANYUMAS TAHUN 2018 - Finish Kuntari; Budi Utomo (Buletin Keslingmas, 2019)
Tuberculosis (TB) Lung is a contagious infectious disease caused by Mycobacterium tuberculosis, the germ enters the human body by breathing air into the lungs. Based on the data of Banyumas District Health Office of 2016, for the work area of Puskesmas I Kembaran, there are new cases of TB + TB patients with 8 people and the total number of cases of Pulmonary TB is 27 people. Therefore it is necessary to observe to know the cause of the incidence of Pulmonary TB disease covering wide of ventilation, lighting, humidity and temperature. The research method used is descriptive observasional that is by describing research variables by doing observation on physical quality of patient of Pulmonary TB with sample number 28 house. Data analysis used is descriptive analysis by using frequency distribution and research variables presented in table form by comparing the result with Decree of Minister of Health of Republic Indonesia Number 829 / MENKES / SK / VII / 1999 concerning Housing Health Requirement.The conclusion is that 28 houses of Pulmonary TB patients in the work area of Puskesmas I Kembaran are categorized as unhealthy house with criteria of house that do not meet health standard